2007
DOI: 10.1080/02772240701228763
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical alterations in rat brain following aluminum exposure: Protection with centrophenoxine

Abstract: Aluminum (Al) is a neurotoxicant potentially affecting ionic, cholinergic, and dopaminergic neurotransmission in the central nervous system. These alterations are known to be associated with learning ability, adaptive responses, and other aspects of behavior. The present experiment was designed to study the neurotoxic consequences of Al exposure on neurotransmitters like dopamine (DA), serotonin (5-HT), norepinephrine (NE) along with the activity of acetylcholinesterase (AChE). Furthermore, Centrophenoxine (Cp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This study showed the possible neuroprotective/neuromodulatory potentials of ESO before and after AlCl 3 exposure on rat's cerebellar morphology and functions through behavioral, biochemical, and histoarchitectural evaluations. The use of neurobehavioral studies in risk assessment is premised on the fact that behavior/emotions can be regarded as the net output of memory, motor, locomotor and cognitive functions occurring in the nervous system and can serve as potentially sensitive endpoints of chemically induced-neurotoxicity [22]. AlCl 3 is a neurotoxicant that permeates and functionally alters the blood-brain barrier and potentially produces changes in the ionic, cholinergic, dopaminergic, and noradrenergic neurotransmission in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed the possible neuroprotective/neuromodulatory potentials of ESO before and after AlCl 3 exposure on rat's cerebellar morphology and functions through behavioral, biochemical, and histoarchitectural evaluations. The use of neurobehavioral studies in risk assessment is premised on the fact that behavior/emotions can be regarded as the net output of memory, motor, locomotor and cognitive functions occurring in the nervous system and can serve as potentially sensitive endpoints of chemically induced-neurotoxicity [22]. AlCl 3 is a neurotoxicant that permeates and functionally alters the blood-brain barrier and potentially produces changes in the ionic, cholinergic, dopaminergic, and noradrenergic neurotransmission in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%